2014
DOI: 10.1007/978-81-322-2208-8_2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Different Feature Extraction Techniques for Offline Malayalam Character Recognition

Abstract: Offline Handwritten Character Recognition of Malayalam scripts have gained remarkable attention in the past few years. The complicated writing style of Malayalam characters with loops and curves make the recognition process highly challenging. This paper presents a comparative study of Malayalam character recognition using 4 different feature sets-Zonal features, Projection histograms, Chain code histograms and Histogram of Oriented Gradients. The performance of these features for isolated Malayalam vowels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…To extract the pixel density features, a method called zoning [27] is employed. Here, the images are partitioned into zones of particular sizes that are predefined such that the features for each zone are measured.…”
Section: 2e Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…To extract the pixel density features, a method called zoning [27] is employed. Here, the images are partitioned into zones of particular sizes that are predefined such that the features for each zone are measured.…”
Section: 2e Densitymentioning
confidence: 99%
“…MSE refers to the average of the squares of values that deviate from the original and is derived from Eq. (27).…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…Similarly, Raveena, et al [38] also suggested a theory related to structural elements (length of character in horizontal and vertical, number of endpoints, number of intersections in horizontal & vertical, number of loops, direction) for feature extraction and SVM for the classification of Malayalam characters. Chacko and Dhanya [39] applied zoning density, projection profile, chain code features, and HOG for feature extraction and compared the performance of all feature extraction methods, with ANN as the classifier. The accuracy achieved using zoning density, projection profile, chain code features, and HOG was 84.6%, 88.07%, 78.8%, and 94.23%, respectively, indicating that HOG recorded the highest accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The technology that will be developed by the research team to help the public in reading Batak script is a technology that applies computer vision and machine learning, namely character classification using the deep learning siamese neural network with one-shot learning [1]. The purpose of this research is to identify Batak script and produce Batak characters and sentences into Batak language using the siamese neural network (SINN) algorithm [2]- [5]. With this application, it is hoped that the community will be able to understand the Batak script so that the Batak script can still be preserved.…”
Section: Introductionmentioning
confidence: 99%